2019
DOI: 10.32800/abc.2019.42.0301
|View full text |Cite
|
Sign up to set email alerts
|

Hidden diversity under morphology–based identifications of widespread invasive species: the case of the ‘well–known’ hydromedusa Craspedacusta sowerbii Lankester 1880

Abstract: 2019. Hidden diversity under morphology-based identifications of widespread invasive species: the case of the 'well-known' hydromedusa Craspedacusta sowerbii Lankester 1880. Animal Biodiversity and Conservation, Doi: https://doi. AbstractHidden diversity under morphology-based identifications of widespread invasive species: the case of the 'wellknown' hydromedusa Craspedacusta sowerbii Lankester 1880. A relatively scarce number of morphological features available for delimiting closely related species and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 61 publications
6
24
0
Order By: Relevance
“…In agreement with Oualid et al (2019), 16S and ITS analyses showed at least 4 main Craspedacusta lineages. According to the identification provided by the different authors to the sequences used (Zhang et al 2009, Zou et al 2012), these species are C. sinensis (for the moment only reported from China), C. ziguiensis (only from China), and 2 separate widespread lineages mainly attributed to C. sowerbii (Collins et al 2008, Fritz et al 2009, Zhang et al 2009, Stefani et al 2010, Zou et al 2012, Karaouzas et al 2015, Failla Siquier et al 2017, Riyas & Kumar 2017, Fuentes et al 2019, Oualid et al 2019. The divergent Cox1 sequence MF000493 from Switzerland could be incorrect -perhaps a nuclear pseudogene, as the 16S sequence places it within one of the 2 main C. sowerbii clades (P. Schuchert pers.…”
Section: Morphological and Phylogenetic Remarks On Bc's Craspedacustasupporting
confidence: 83%
See 4 more Smart Citations
“…In agreement with Oualid et al (2019), 16S and ITS analyses showed at least 4 main Craspedacusta lineages. According to the identification provided by the different authors to the sequences used (Zhang et al 2009, Zou et al 2012), these species are C. sinensis (for the moment only reported from China), C. ziguiensis (only from China), and 2 separate widespread lineages mainly attributed to C. sowerbii (Collins et al 2008, Fritz et al 2009, Zhang et al 2009, Stefani et al 2010, Zou et al 2012, Karaouzas et al 2015, Failla Siquier et al 2017, Riyas & Kumar 2017, Fuentes et al 2019, Oualid et al 2019. The divergent Cox1 sequence MF000493 from Switzerland could be incorrect -perhaps a nuclear pseudogene, as the 16S sequence places it within one of the 2 main C. sowerbii clades (P. Schuchert pers.…”
Section: Morphological and Phylogenetic Remarks On Bc's Craspedacustasupporting
confidence: 83%
“…Dejdar's anatomical and nematocyst information are from some medusae collected in Vltava (Moldau close to Libčice, Czech Republic). However, BC specimens of C. sowerbii are quite similar to those examined by Oualid et al (2019) from North Africa, but both sets of samples are, from a phylogenetic point of view (mitochondrial and nuclear markers), widely separated clades (Figs. 4,S1 & S2), sometimes separated by different Craspedacusta species (Fig.…”
Section: Morphological and Phylogenetic Remarks On Bc's Craspedacustamentioning
confidence: 66%
See 3 more Smart Citations